Preliminary Research Findings from Trade Ceramic Archaeological Sites in Sabah - Azman, Nurulnatasha; Abdullah, Jeffrey (School of Social Sciences, 2015)
Ceramics is one of the most important merchandise in the past. In Sabah, many trade ceramic wares were found in archaeological sites. The study of trade ceramics in Sabah and its distribution enables the types of ceramic wares were identified and their distribution by region in Sabah. Therefore, in order to achieve this objective, whole sites with the imported ceramic in Sabah has been divided into the following four main areas including east, west, north and interior of Sabah. Results from the analysis showed that most of ceramics that were found came from China, Europe, Netherlands, Vietnam and Thailand. While the age of ceramics is from the Song dynasty (10-13 century AD), Yuan (13-14 century AD), Ming (14 -17 century AD) and Ching (17-20 century AD), Thailand (14-15 century AD), Vietnam (14-15 century AD), Europe and the Netherlands (19-20 century AD). All of this discovery shows that the distribution of the ceramic sites may have been connected with other countries via trading activities especially in the coastal areas in Sabah